2020
DOI: 10.17275/per.20.34.7.3
|View full text |Cite
|
Sign up to set email alerts
|

Pursuing STEM Careers: Perspectives of Senior High School Students

Abstract: This qualitative descriptive research explored the perspectives of STEM (science, technology, engineering, and mathematics) senior high school students in a public secondary school in Zambales, Philippines on their reasons why they enrolled in STEM and their intent to pursue relevant career. A total of 20 Grade 12 students were purposively selected as participants of the research. The participants were interviewed using a validated structured interview guide. The recorded interviews were individually transcrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…This is congruent with the Philippine science education under the K to 12 curriculum which puts science education at the core of emerging scientific literacy among learners that will formulate them to be knowledgeable and participative citizens who can formulate verdicts and concerning applications of scientific knowledge that may have social, health, or environmental impacts [1]. STEM education had contributed vital importance in building the nation's productivity [15].…”
Section: Introductionmentioning
confidence: 82%
“…This is congruent with the Philippine science education under the K to 12 curriculum which puts science education at the core of emerging scientific literacy among learners that will formulate them to be knowledgeable and participative citizens who can formulate verdicts and concerning applications of scientific knowledge that may have social, health, or environmental impacts [1]. STEM education had contributed vital importance in building the nation's productivity [15].…”
Section: Introductionmentioning
confidence: 82%
“…When we delved into analyzing why students would choose STEM degrees, we noticed a significant gender difference from the “earn a lot of money” option, despite the fact that some research has shown that salary is one of the reasons why students choose certain studies regardless of gender (Rafanan et al, 2020 ). Therefore, this gender difference should be further analysed and cross-checked with other personal or motivational variables, as STEM jobs tend to have a better projection and salary.…”
Section: Discussionmentioning
confidence: 99%
“…5 Alignment to the chosen college course was the main reason of students enrolling in the STEM strand. 6 Besides, a study found that STEM status significantly predicted retention and graduation outcomes. 7 Poor adjustment and academic performance to the health science courses also contribute to dropout rates of students.…”
Section: Introductionmentioning
confidence: 99%